Exploring the Utility of Trello – An Alternative Learning Management System in Facilitating Problem-Based Learning in Medical Education - Salakay, Elisa Nugraha Haryadi; Shrivastava, Saurabh RamBihariLal (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2024)
Background: The increasing utilization of technology in medical education calls for innovative learning media that can effectively support teaching and learning processes. Exploring alternative Learning Management System (LMS) options is necessary because some LMSs have cost customization and usability limitations.Aim: This review explores the potential utility of Trello, an alternative LMS, as a tool for facilitating Problem-Based Learning (PBL) in medical education.Learning Media Review: Trello, a flexible and user-friendly LMS based on Kanban, provides features like boards, lists, and cards that users can customize to create tutorial learning processes. Trello facilitates student-centered learning, collaboration, active learning, communication, and critical thinking, all essential principles in PBL. It enables synchronous and asynchronous learning sessions, allows tutors to monitor and interact with students, and provides centralized organization and tracking of tasks and progress.Conclusion: Trello demonstrates excellent potential as an alternative LMS in medical education. Its adaptable features, seamless integration with various technologies, and user-friendly interface make it an engaging platform for educators and learners. Trello effectively supports the implementation of PBL tutorials, mainly using the Seven Jump method. However, we should consider user training, accessibility, and inclusivity. Further research is recommended to explore assessment methods, enhance student engagement, and assess long-term implementation and sustainability.